BETON BERMUTU DAN RAMAH LINGKUNGAN DENGAN MEMANFAATKAN LIMBAH ABU CANGKANG SAWIT - Johan Oberlyn Simanjuntak; Tiurma Elita Saragih; Partahi Lumbangaol; Sintong Petrus Panjaitan (Jurnal Darma Agung, 2020)
Concrete is the main material for construction which is widely used throughout the world. However, with the increase in the use of concrete from time to time which causes the amount of available resources to decrease and will also disturb the environmental balance, an alternative that can be used to overcome this is to get environmentally friendly concrete which reduces the use of cement utilizing the results of industrial wastes. One of them is the utilization of oil palm shell ash waste. Palm shell ash is expected to be used as an additive to the concrete mixture. In this study, palm kernel shell ash was used as an additive to cement with a mixture of 0%, 3%, 6%, 9% by weight of cement. The number of test objects is 3 cylinders for each variation of the mixture. The type of test carried out is in the form of the compressive strength of the concrete and the observation of the test object is carried out at the age of 7 days, 14 days, 21 days, and 28 days. From the research results, it was found that the increase in the value of the compressive strength of concrete on the variation of the addition of palm shell ash waste as an added material to cement to create quality and environmentally friendly concrete.